The Balance Between Board Monitoring and Advising: The Role of Social Capital - Zhe Li (European Financial Management Association Meeting, 2021)
We investigate how social capital, captured by the strength of cooperative norms and social networks within a geographical community, affects the internal organization of boards. We find that firms headquartered in high-social-capital communities have a more advisory-focused internal board structure as they are more likely to set up specialized advisory committees and appoint more advisory directors. These findings are robust to instrumental variable analysis, propensity score matching, difference-in-differences analysis, alternative measures, and time-invariant firm characteristics. Additionally, the positive influence of social capital on board advisory focus is more palpable for firms with greater advisory needs and lower monitoring needs. Overall, our results are consistent with the interpretation that social capital serves as a societal monitoring mechanism to reduce board monitoring needs and, thus, boards of firms located in high-social-capital communities focus more on the advising function.